Effectively using data for educator preparation program improvement - Gorowara, Christine Carrino; Brownstein, Erica M.; Wall, Timothy J., 1972- (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"This volume provides a synthesis of protocols, and strategies to support assessment leaders in effectively using data for educator preparation program improvement. Data-informed decision-making has become increasingly important in quality assurance for both internal and external audiences, yet there are scant resources to guide those charged with managing the development and application of data for monitoring and improving the quality of their programs. Until this work, there has been little explication of how assessment directors working in educator preparation should conceptualize, organize, and implement best practices in data collection, analysis, interpretation, and sharing. As state and national expectations for evidence of quality are growing, it is essential to chronicle the collective wisdom of assessment leaders in education preparation in one manuscript. For both novice and experienced assessment directors, this volume offers insightful perspectives and excellent strategies to facilitate the journey from complying with external expectations to strategically using data and evidence to achieve goals, leveraging assessment to achieve socially just outcomes, involving multiple voices and interpreters, and opening windows to further inquiry. The editors have gathered experts in all phases of the assessment process and organized their work in an easy-to-follow manner. This work provides both conceptual underpinnings of educator preparation quality assurance as well as practical lessons learned that will support the transformation of an assessment professional into an assessment leader"-- Provided by publisher.
Keywords: Teachers -- Training of -- United States -- Evaluation.; Educational evaluation -- United States -- Data processing.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books